Persiapan Kedatangan Mesias Selama Masa Intertestamental - Nicko Hosea Layantara (Manna Rafflesia, 2022)
The intertestamental era was a 400 years period between Old Testament and New Testament when God didn’t say anything to the Israelites. Connected with the promise in the Old Testament that the Lord would send the Messiah who would save his people, would it be difficult fulfilled by the intertestamental era? This article wants to explain the things that happened during the intertestamental era, especially about the fulfillment of the messianic promise. The research method that is used in this article is the qualitative method, by using a literature study with the descriptive analysis approach. The intertestamental era was a period in which God worked to prepare the coming messiah. Some works that God did in the intertestamental era: God made the Israelites repent, God held the remnant of Israelites to be the ancestor of the messiah, God used the Ptolemy dynasty to drive the writing of Septuagint that contained the messianic promise, God used Herod the Great until Herod Antipas to permit the Israelites resided in their land for the sake of the birth and the ministry of the messiah, God used the Hellenization for the spreading of the Gospel to the Greek, moreover God used the Romans in preparing the writing of the books of the New Testament, which contained the news of the messiah. The conclusion, in the intertestamental era, God prepared the coming of the messiah by holding the existence of the Israelites and making them repent, letting the Israelites go back to their land, and preparing the spreading of the news of the messiah in other languages.